Rapid and sensitive determination of doxorubicin in human whole blood by vertically-ordered mesoporous silica film modified electrochemically pretreated glassy carbon electrodes. Issue 15 (1st March 2021) - Wang, Meifang; Lin, Jing; Gong, Jiawei; Ma, Mingchen; Tang, Hongliang; Liu, Jiyang; Yan, Fei
Abstract : Direct and accurate detection of doxorubicin (DOX) in unprocessed human whole blood is of vital importance in medical diagnosis and monitoring. Abstract : Direct and accurate detection of doxorubicin (DOX) in unprocessed human whole blood is of vital importance in medical diagnosis and monitoring. In this work, we demonstrate the utilization of electrochemically pretreated glassy carbon electrodes (p-GCE) modified with vertically-ordered mesoporous silica films (VMSF) for rapid and sensitive electrochemical detection of DOX. The electrochemically pretreated process is a simple, cost-effective and environmentally friendly approach for improving interface catalytic properties and introducing oxygen-containing groups into the GCE surface, which could be suitable for stably growing VMSF without any adhesive layer simultaneously retaining the underlying electrode activity. Benefiting from the highly sensitive electrode substrate of p-GCE and electrostatic preconcentration effect of VMSF, the present VMSF/p-GCE sensor was able to determine DOX with an ultrahigh sensitivity (23.94 μA μM −1 ) and a relatively low limit of detection (0.2 nM) and a rather wide linear range (0.5 nM to 23 μM). Furthermore, direct and reliable electrochemical detection of DOX in human whole blood without complicated sample pretreatments was achieved owing to the excellent anti-fouling and anti-interference ability of VMSF.